Expected lifetime range ratio to find mean reversion: Evidence from Indian stock market - Muneer Shaik; S. Maheswaran (Cogent Economics & Finance, 2018)
We use the expected lifetime range (ELR) ratio based on the extreme values of asset prices to detect the presence of mean reversion in stock returns. We find that the actual cross-sectional average of the ELR ratio is significantly less than its bootstrap means, thereby indicating a considerable amount of mean reversion. We argue that ELR ratio is more conclusive in detecting mean reversion when compared to the traditional Lo and MacKinlay variance ratio variance ratio. On the empirical side, we find that mean reversion is a robust feature among the constituents of India's BSE SENSEX stock index.
Keywords: C12; C15; C58; G10; 330; mean reversion; extreme value estimators; expected lifetime range ratio; Lo and MacKinlay variance ratio; random walk